Exploring the association between 91 circulating inflammatory proteins and the risk of carcinoid syndrome: a Mendelian randomization analysis - Jingzhi Wang; Simin Peng (Discover Oncology)
Abstract This study aims to explore the potential correlation between circulating inflammatory proteins and carcinoid syndrome (CS). Using summary data from genome-wide association studies (GWAS), we conducted a Mendelian randomization (MR) analysis with two samples, treating 91 circulating inflammatory proteins as exposure factors and CS as the outcome. Based on genetic loci closely associated with circulating inflammatory proteins selected as instrumental variables, we primarily employed the inverse-variance weighted (IVW) method for analysis, combined with the weighted median method (WM), simple median method (SM), weighted mode estimation (WME), and MR-Egger regression for comprehensive analysis. Initial IVW results revealed significant causal effects of six circulating inflammatory proteins on CS. Specifically, Interleukin-17C levels were negatively correlated with CS risk, indicating a protective effect; whereas beta-nerve growth factor, C-C motif chemokine 20, Natural killer cell receptor 2B4, C-X-C motif chemokine 5, and Leukemia inhibitory factor levels were positively correlated with CS risk, suggesting detrimental effects. In heterogeneity tests, the selected single-nucleotide polymorphisms (SNPs) did not show heterogeneity, and analysis using Egger intercept and MR-PRESSO test did not detect pleiotropy of SNPs, thus validating the reliability of the study. Furthermore, sensitivity analysis using the leave-one-out method further confirmed the robustness of the results. In summary, this study identified significant causal relationships between six inflammatory proteins—Interleukin-17C, beta-nerve growth factor, C-C motif chemokine 20, Natural killer cell receptor 2B4, C-X-C motif chemokine 5, and Leukemia inhibitory factor—and CS risk through MR analysis. This finding not only emphasizes the important role of inflammation in the pathogenesis of CS but also suggests the potential value of inflammatory proteins as targets for early diagnosis and therapeutic interventions.